PERCEPTIONS OF TRADITIONAL MEDICINES FOR SELF-MEDICATION AMONG PEOPLE IN DIENG PLATEAU CENTRAL JAVA PROVINCE, INDONESIA - Aris Widayati; Damiana Sapta Candrasari; Lusia Jois Mariana; Veronica Veronica (Jurnal Riset Kesehatan, 2021)
Traditional medicines are commonly used in the community. One type of traditional medicines that is popular among people is "jamu". "Jamu" can be made from plants, animals, minerals, or a mixture of them that has been used for generations based on empiric experience. This study aimed to describe perceptions of the use of traditional medicines for self-medication among people in Dieng Plateau, Kejajar, Wonosobo, Central Java Province. This is a descriptive study with a qualitative approach. Respondents were adults more than 18 years old who had experience in using traditional medicines and were selected with non-random accidental sampling. Thirty-one (31) respondents signed informed consent. Data were collected using an interview guideline and analyzed using enumerative approach. Most of the respondents used traditional medicines for self-medication one to five times a month. They expressed that traditional medicine is like "Jamu", primarily liquid, with limited or no side effects. Traditional medicine was mostly obtained from local groceries at affordable prices. Most of the respondents have a positive attitude towards the use of traditional medicines. They have the willingness to use traditional medicines to deal with their symptoms or minor illnesses. Their satisfaction experience in using traditional medicine will motivate them to do so in the future. Based on the results, it can be said that traditional medicines have an important role in the health care system particularly for self-medication.